Development of an Assessment Instrument for Beginning Reading for Moderately Mentally Disabled Children in Grade VIII at SLB ABC Miiroojuttaqwaa - Rohimat, Mamat; Hidayat, Ayi Najmul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a contextual early reading assessment instrument tailored for eighth-grade students with moderate intellectual disabilities at SLB ABC Miiroojuttaqwaa in Sumedang Regency. Using a qualitative approach and descriptive methods, the research involved non-participatory observations, interviews, focus group discussions (FGD), documentation studies, and validation by expert teachers. The results reveal that students demonstrate varying levels of competence in phonemic recognition, syllable decoding, and vocabulary comprehension but face difficulties with sentence construction and reading fluency. The assessment instrument was refined collaboratively through FGDs, covering core reading domains, and validated by external experts for operational clarity and usability. Key improvements include more concrete indicators, enhanced visual media, and implementation guidelines to standardise administration. The findings highlight the importance of authentic, adaptive assessments that align with cognitive and developmental characteristics of students with intellectual disabilities. This tool not only supports the development of Individualised Education Plans (IEPs) but also provides a model for inclusive assessment practices. The study recommends broader institutional adoption, including integration into policy frameworks, professional development for teachers, and cross-school moderation, to enhance reliability and equity. The validated instrument holds promise for advancing literacy interventions and promoting meaningful participation in education for students with intellectual disabilities.